Company Financial Performance Based On CSR Communication Via Social Media Review From Customer’s Engagement And Electronic-Word Of Mouth (e-WOM) - Fauziyyah, Nurul; Ersyafdi, Ilham Ramadhan; Ulfah, Fitriah; Hudori, Ahmad Hudri; Afifah, Sintia Nur; Hanifah, Mariska Nur (Journal of Ecohumanism, 2024)
In recent years, Corporate Social Responsibility (CSR) has garnered significant attention from society and the business world. Beyond profit-making, companies are increasingly expected to contribute to community welfare and environmental sustainability. However, a prevalent challenge is the perception of CSR as merely a compliance measure, often seen as an additional cost rather than a strategic advantage. This study explores CSR communication through social media, emphasizing its role in fostering customer engagement, enhancing electronic word-of-mouth (e-WOM), and positively influencing financial performance. The research investigates the effectiveness of various social media platforms in CSR communication, particularly newer platforms, and evaluates their impact on consumer behavior and company reputation. Primary data were collected through questionnaires distributed to 232 respondents, while secondary data were derived from 17 companies in the Consumer Goods Industry sector, covering sub-sectors such as Food and Beverages, Pharmaceuticals, and Cosmetics. Using SmartPLS SEM, the study confirms that CSR communication via social media positively affects financial performance, with customer engagement and e-WOM serving as critical mediators. While e-WOM’s direct effect on financial performance is insignificant, its interaction with customer engagement and social media amplifies results. This research offers novel insights into the strategic integration of CSR and social media to drive business success.